Mechanical rolling of nickel nanowire-PVDF composites yields enhanced conductivity and electromagnetic shielding properties - Meghana Jois H S; Amanuel Gebrekrstos; Anastasia Elias (Results in Engineering)
Highly flexible and lightweight PVDF-based nickel nanowires (NiNWs) composites are promising candidates for electronic devices, particularly in electromagnetic shielding. However, the alignment of NiNWs within the PVDF matrix to achieve high electrical conductivity presents a significant challenge. In this study, we present a straightforward and scalable method to prepare aligned NiNWs-PVDF composites using mechanical shear force (i.e., rolling). We firstly synthesized conductive, high aspect ratio NiNWs; we then prepared thin films of PVDF/NiNWs composites with various NiNWs concentrations (40–70 wt.%) via solution casting. These solution-cast PVDF/NiNWs composites were then mechanically rolled, and alignment of the NiNWs and PVDF lamellae was achieved, as confirmed by TEM and SAXS images. The oriented NiNWs in the PVDF matrix exhibited superior electrical conductivity compared to solution-cast samples without mechanical rolling. Notably, the percolation threshold of the rolled films was lower than that of the samples that were not rolled. Furthermore, the rolling process increased both the β-phase formation and the overall crystallinity of the PVDF matrix, as evidenced by FTIR and DSC analyses, respectively. Owing to enhancement of conductivity and dielectric permittivity, rolled composites displayed a total shielding efficiency of -42 dB over the 12 – 18 GHz frequency band (relevant to satellite and microwave communications), compared with -32 dB for non-rolled (solution cast) samples. This performance can be attributed to an absorption-dominant shielding mechanism due to the enhancement of interfacial polarization and β-phase formation. Mechanically rolled films are good candidates for use in EMI shielding applications requiring thin and lightweight materials.